Effect of classical and molecular production techniques on physical properties and volatile compounds of berry ice-creams - Aydın, Mehmet (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2023)
This study aims to investigate some chemical, physical, textural, and aroma compounds properties of the ice-cream with berry fruits produced using classical and molecular ice-cream production techniques. No significant difference was determined between the pH, dry solid, fat, protein, ash amounts, and overrun of the samples. However, molecular ice-creams, in particular, have a softer structure since they contain tiny ice crystals, and the first dripping and full melting time was realized in less time. The effect of added fruit variety on the viscosity value of the samples was found to be significant. It was observed that the volatile compound profiles of the ice-creams were affected differently by ice-cream production techniques. The octanoic, hexanoic, and dodecanoic acid were high-value prominent compounds in all the ice creams. Furthermore, the 14 volatile compounds that are effective in the difference between the ice-creams and their production techniques were determined, which is more important in the ice cream aroma. This is the first study on the change of the volatile compounds, hence the aroma compound profile, in molecular ice-cream production technique. And, it was presented as an innovative approach. Therefore, it is thought to be shed new light on future studies